2008
DOI: 10.1093/intimm/dxn066
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Melan-A reactive memory CD8+ T cells in a healthy donor

Abstract: Melan-A specific CD8+ T cells are thought to play an important role against the development of melanoma. Their in vivo expansion is often observed with advanced disease. In recent years, low levels of Melan-A reactive CD8+ T cells have also been found in HLA-A2 healthy donors, but these cells harbor naive characteristics and are thought to be mostly cross-reactive for the Melan-A antigen. Here, we report on a large population of CD8+ T cells reactive for the Melan-A antigen, identified in one donor with no evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 39 publications
(40 reference statements)
1
22
1
Order By: Relevance
“…We observed both naïve and central memory MELOE-1-specific T cells in healthy donors and melanoma patients. The presence of MELOE-1 memory-specific T cells in healthy donors could result from a stimulation through cross-reactive peptides as previously described for the Melan-A antigen in one HLA-A2 1 healthy donor [29]. These Melan-Aspecific cells, likely generated through a stimulation with crossreactive peptides, turned out to be reactive against melanoma cells.…”
mentioning
confidence: 67%
“…We observed both naïve and central memory MELOE-1-specific T cells in healthy donors and melanoma patients. The presence of MELOE-1 memory-specific T cells in healthy donors could result from a stimulation through cross-reactive peptides as previously described for the Melan-A antigen in one HLA-A2 1 healthy donor [29]. These Melan-Aspecific cells, likely generated through a stimulation with crossreactive peptides, turned out to be reactive against melanoma cells.…”
mentioning
confidence: 67%
“…1A). Molecular replacement was successful only in space group P4 3 , consistent with the presence of one molecule of the complex per asymmetric unit, and the resolution was sufficiently high to show that the interface between the two molecules was well ordered and contained well defined electron density. The final model showed ϳ96% of residues in the preferred and allowed regions of the Ramachandran plot and geometry consistent with the data resolution.…”
Section: Structure Determination and Analysis Of Mel5 In Complex Withmentioning
confidence: 96%
“…The MART-1 (1) protein, also known as Melan-A (2), is expressed by virtually all fresh melanoma tumor specimens and elicits natural CD8 ϩ T-cell responses (3,4) that can lead to spontaneous disease regression (reviewed in Ref. 5).…”
mentioning
confidence: 99%
“…We have shown that the natural Melan-A [26][27][28][29][30][31][32][33][34][35] decapeptide binds weakly to the HLA-A2 molecule because of the lack of a strong anchor residue at position P2. The replacement of Ala at position 27 for Leu results in enhanced binding to HLA-A2, in 2-to 3-log increase of its relative antigenicity and, more importantly, to an increased immunogenicity (17).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HLA-DQ6/ Melan-A 25-36 multimers directly identified specific CD4 T cells by flow cytometry. Interestingly, this optimal CD4 T-cell epitope fully encompasses the HLA-A2-restricted decapeptide Melan-A [26][27][28][29][30][31][32][33][34][35] . In this report, we used HLA-DQ6/Melan-A peptide multimers to analyze in detail Melan-A-specific CD4 T-cell responses in healthy individuals (HD) and a cohort of HLA-A*0201 metastatic melanoma patients who shared expression of the HLA-DQB1*0602 allele.…”
Section: Introductionmentioning
confidence: 99%